Enhancing Biodegradable Plastics' Physical Properties Through the Incorporation of Talas Beneng Starch (Xanthosoma undipes K. Koch) and Glycerol as a Plasticizer - Maghfirah, Awan; Sudiati, Sudiati; Ramadina, Silvia; Pratiwi, Dwi Ajeng (Talenta Publisher, 2023)
The manufacture of biodegradable plastics with the main ingredients of talas beneng (Xanthosoma Undipes K. Koch) starch, chitosan, and glycerol as a plasticizer has been carried out by various additions of starch and reduction of chitosan. Initial assessment of talas beneng starch reveals: starch content - 20.51%, water content - 8.58%, fat content - 12.71%, and protein content - 3.51%. Physical testing of biodegradable plastic produces thickness values ranging from 0.166 mm to 0.234 mm, tends to meet JIS Z-1707: 2019 standards, density value is 1.674 g/cm3, and the lowest water absorption value is 20.51%, both meet SNI 7188: 2016 standards, and there is a decrease in mass every week for 28 days in the biodegradation test.